Estabilidade em implantes dentários: análise da frequência de ressonância e torque de inserção - Frederico Santos Lages (2017)
Clinical research in the implantology presents a great difficulty regarding the evaluation of the osseointegration and stability of the implants. Thus, resonance frequency analysis (RFA) has become one of the main tools used, since it offers, in a simple and non-invasive way, the possibility of monitoring the stability during the desired period. Another measure also widely used in clinical practice is the insertion torque of the implants. However, this measure is limited to the trans-surgical and provides only the primary stability of the implants, which makes it more suitable for evaluating the possibility of undergoing immediate loading. This study aims to evaluate, through a cross-sectional study, whether implant stability coefficient (ISQ) values are similar at different heights of the prosthetic component and directly on the platform, when measured through RFA and evaluated by means of a systematic review and meta-analysis of the relationship between the insertion torque and the RFA, investigating whether these two instruments provide similar assessments of the primary stability of the same implant. For this purpose, a cross-sectional study was performed on 31 osseointegrated implants with external hexagon platform, 4.1 mm in diameter and length greater than or equal to 10 mm and a systematic review with clinical trials that reported ISQ values and insertion torque values. Thus, our studies recommend that exploring and developing RFA as a method of evaluating implant stability should be a still necessary search of scientific research to better understand the behavior of dental implants in their various moments and situations in the oral cavity, as well as to determine a a good level of stability which would consequently determine the greater longevity and functionality of dental implants. Keywords: Osstell; Ressonance Frequence Analysis; Insertion Torque; Dental Implants.